Predicting future self-harm or suicide in adolescents: a systematic review of risk assessment scales/tools - Isobel Marion Harris; David Moore; Sophie Beese (BMJ Open)
Objective This systematic review aimed to evaluate the ability of risk tools to predict the future episodes of suicide/self-harm in adolescents.Design Systematic review.Data sources MEDLINE, EMBASE, CINAHL and PsycINFO were searched from inception to 3 March 2018.Eligibility criteria for selecting studies Cohort studies, case–control studies and randomised controlled trials of adolescents aged 10–25 who had undergone risk assessment in a clinical setting following an episode of self-harm were included.Data extraction and synthesis Two independent reviewers extracted data and assessed risk of bias. Data were grouped by tool and narrative synthesis undertaken, with studies appraised using a checklist combining the QUIPS (Quality In Prognosis Studies) and QUADAS-2 (Quality Assessment of Diagnostic Accuracy Studies) tools.Results Of the 17 137 articles initially identified, 11 studies evaluating 10 separate tools were included. The studies varied in setting, population and outcome measure. The majority of the studies were rated as having an unclear risk of bias, and meta-analysis was not possible due to high variability between studies.The ability of the tools to correctly identify those adolescents going on to make a self-harm/suicide attempt ranged from 27% (95% CI 10.7% to 50.2%) to 95.8% (95% CI 78.9% to 99.9%). A variety of metrics were provided for 1–10 points increases in various tools, for example, odds and HRs.Conclusions This systematic review is the first to explore the use of assessment tools in adolescents. The predictive ability of these tools varies greatly. No single tool is suitable for predicting a higher risk of suicide or self-harm in adolescent populations.PROSPERO registration number CRD42017058686